Neutralisation techniques in the control of forced labour: the case of the ILO engagement in Uzbekistan = Neutralisierungstechniken bei der Kontrolle von Zwangsarbeit: der Fall des ILO-Einsatzes in Usbekistan - Kreuels, Benedict (Kriminologie - das Online-Journal, 2025)
This paper focuses on forced labour in Uzbekistan’s cotton harvest. It uncovers and deconstructs the narratives of organisational actors in the process of combating this form of state crime. We employ a deductive qualitative analysis of the International Labour Organisation’s (ILO’s) third-party harvest monitoring reports (2015 to 2022) and find that the ILO employs neutralisation techniques in its communication to ensure ongoing cooperation with the Uzbek government. Our findings reveal a paradox: The neutralisation-and trust-based mode of cooperation chosen by the ILO was seemingly effective in improving the labour rights situation during the cotton harvest. However, it also had a stabilising, integrating,and legitimising effect on the Uzbek government, providing it with an overall “clean bill of health” regarding human rights, and in the process, possibly obscuring transgressions in other sectors.